Genome-Wide Expression Profiling Arabidopsis at the Stage of Golovinomyces cichoracearum Haustorium Formation - Fabro, Georgina (2008)
Compatibility between plants and obligate biotrophic fungi requires fungal mechanisms for efficiently obtaining nutrients andcounteracting plant defenses under conditions that are expected to induce changes in the host transcriptome. A key step in theproliferation of biotrophic fungi is haustorium differentiation. Here we analyzed global gene expression patterns in Arabidopsisthaliana leaves during the formation of haustoria by Golovinomyces cichoracearum. At this time, the endogenous levels of salicylicacid (SA) and jasmonic acid (JA) were found to be enhanced. The responses of wild-type, npr1-1, and jar1-1 plants were used tocategorize the sensitivity of gene expression changes to NPR1 and JAR1, which are components of the SA and JA signalingpathways, respectively. We found that the infection process was the major source of variation, with 70 genes identified ashaving similarly altered expression patterns regardless of plant genotype. In addition, principal component analysis (PCA)identified genes responding both to infection and to lack of functional JAR1 (17 genes) or NPR1 (18 genes), indicating that theJA and SA signaling pathways function as secondary sources of variation. Participation of these genes in the SA or JA pathways had not been described previously. We found that some of these genes may be sensitive to the balance between the SA and JA pathways, representing novel markers for the elucidation of cross-talk points between these signaling cascades.Conserved putative regulatory motifs were found in the promoter regions of each subset of genes. Collectively, our results indicate that gene expression changes in response to infection by obligate biotrophic fungi may support fungal nutrition by promoting alterations in host metabolism. In addition, these studies provide novel markers for the characterization of defense pathways and susceptibility features under this infection condition.